2014
DOI: 10.1002/ijc.28800
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 signaling couples to Bim and not Bmf to discriminate subsets of alveolar rhabdomyosarcoma cells

Abstract: Biological heterogeneity represents a major obstacle for cancer treatment. Therefore, characterization of treatment-relevant tumor heterogeneity is necessary to develop more effective therapies in the future. Here, we uncovered population heterogeneity among PAX/FOXO1-positive alveolar rhabdomyosarcoma by characterizing prosurvival networks initiated by FGFR4 signaling. We found that FGFR4 signaling rescues only subgroups of alveolar rhabdomyosarcoma cells from apoptosis induced by compounds targeting the IGF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…This indicates that furin silencing primarily triggers the intrinsic apoptotic pathway. Others have shown that disruption of the IGF1R and/or PI3K/mTOR pathways leads to apoptosis in Rh3 and Rh4 cell lines [12, 33]. In this study we found evidence that activation of the IGF signaling pathway is dependent on furin activity.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This indicates that furin silencing primarily triggers the intrinsic apoptotic pathway. Others have shown that disruption of the IGF1R and/or PI3K/mTOR pathways leads to apoptosis in Rh3 and Rh4 cell lines [12, 33]. In this study we found evidence that activation of the IGF signaling pathway is dependent on furin activity.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, we examined the cell cycle distribution of Rh4 and Rh3 cells 72h after DOX treatment and found a clear increase of cells in sub-G1 phase (Figure 3A - shFAi: 54-62%, shFEi: 26-32%). As a positive control for apoptosis we treated aRMS cells with a combination of 1 μM of the IGF1R-inhibitor AEW451 (AEW) and 275 nM of the dual PI3K/mTOR inhibitor BEZ235 (BEZ) for 24h, conditions that induce apoptosis in aRMS cell lines [33]. As expected, treatment with BEZ/AEW led to an increase of cells in sub-G1 phase (Figure 3A - Rh4: 22%, Rh3: 18%).…”
Section: Resultsmentioning
confidence: 87%
“…Preselection was based on number of unique peptides identified by MS combined with possible function as described in the literature. Additionally, we used gene expression data from different FP-RMSs to include only candidates with detectable expression levels (24). RH4 cells, whose gene expression signature represents most closely tumor biopsies (19,33), were individually transfected with 3 unique siRNA sequences per target and transcript levels of 5 PAX3-FOXO1 target genes measured after 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Many putative therapeutically relevant signaling pathways have been described with varying degrees of tumor cells' dependence on them and therefore also varying tumor response upon inhibition. Also, their complexity, crosstalk, and acquired drug resistance often limit clinical application of drugs targeting key components of these pathways (23)(24)(25). Furthermore, pediatric cancers in general are known to carry very few mutations compared with adult tumors, and recent comprehensive genomic analysis has identified a particularly low overall mutational burden in FP-RMS, decreasing the number of potential actionable targets and underscoring the importance of the fusion proteins as dominant driver (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…FGFR4 protein is expressed in the two main variants of RMS—embryonal RMS and alveolar RMS (aRMS). Interestingly, only certain subgroups of aRMS cells are rescued by FGFR4 signaling following induction of apoptosis by compounds targeting the IGF1R-PI3K-mTOR pathway [3032]. Therefore, expression patterns of FGFRs could facilitate selection of patients for adjuvant systemic therapy.…”
Section: Discussionmentioning
confidence: 99%